Assessing the Economic Value of Venture Capital Contracts An Option Pricing Approach - Onimus, Jil Caroline; SpringerLink (Online service) (Wiesbaden : Gabler, 2011)
Jil C. Onimus makes a contribution to the nascent research line on the economic value of venture capital contracts which lies at the intersection of venture capital contract design and real option pricing. She identifies the baskets of real options embedded in model venture capital contracts as published by the National Venture Capital Association (NVCA) and shows how they can be priced in interaction using Least Squares Monte Carlo simulation. The pricing model is calibrated by means of a dataset of deal terms in Silicon Valley as well as industry statistics from the NVCA. By applying the model to standard investment scenarios (multiple financing rounds with multiple investors), the author obtains estimates of option values for individual terms and for full contracts with interaction effects.
Keywords: Economics; Economics/Management Science; Finance/Investment/Banking.